2015
DOI: 10.1101/gad.268961.115
|View full text |Cite
|
Sign up to set email alerts
|

FGF2 mediates hepatic progenitor cell formation during human pluripotent stem cell differentiation by inducing the WNT antagonist NKD1

Abstract: Fibroblast growth factors (FGFs) are required to specify hepatic fate within the definitive endoderm through activation of the FGF receptors (FGFRs). While the signaling pathways involved in hepatic specification are well understood, the mechanisms through which FGFs induce hepatic character within the endoderm are ill defined. Here we report the identification of genes whose expression is directly regulated by FGFR activity during the transition from endoderm to hepatic progenitor cell. The FGFR immediate ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…However, it is important to note that cell death per se should not be considered a criterion for exclusion because disruption of many developmentally important pathways can manifest in a cell death phenotype. For example, acute inhibition of FGF signaling blocks specification, but when the FGFR is chronically repressed it diminishes cell viability (Twaroski et al, 2015). With this in mind, if we avoid exclusion based solely on viability, several additional small molecules could be considered provocative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is important to note that cell death per se should not be considered a criterion for exclusion because disruption of many developmentally important pathways can manifest in a cell death phenotype. For example, acute inhibition of FGF signaling blocks specification, but when the FGFR is chronically repressed it diminishes cell viability (Twaroski et al, 2015). With this in mind, if we avoid exclusion based solely on viability, several additional small molecules could be considered provocative.…”
Section: Discussionmentioning
confidence: 99%
“…In our screen, treatment with such small molecules usually resulted in a detrimental effect on cell viability as evidenced by loss of DAPI staining. We also identified small molecules targeting signaling pathways that are necessary for hepatic progenitor cell formation from pluripotent stem cells, including the FGF (PD161570) and WNT (XAV939) pathways (Twaroski et al, 2015). In addition to the known pathways, several of the small molecules that affected HNF4A protein levels were agonists or antagonists of kinases or signaling receptors.…”
Section: −26mentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, numerous novel FGF‐dependent immediate early genes whose expression was elevated during the specification of hepatic cells from the endoderm were identified. These studies revealed that the WNT signaling inhibitor naked cuticle homolog 1 was an FGFR immediate early gene that was essential for the transition of the endoderm to a hepatic fate …”
Section: Pscs As a Model Of Liver Developmentmentioning
confidence: 99%
“…The JAK2 gene has been implicated in cytokine receptor signaling pathways and was identified to be associated with the reactions to human interferon-γ (29). The FGF2 protein is a member of the FGF family and is involved in wound healing, limb and nervous system development, and carcinoma growth (30). POLR2A encodes the largest subunit of RNA polymerase II, the product of this gene includes a carboxy-terminal domain composed of heptapeptide repeats, which are required for polymerase activity (31).…”
Section: Ppi Network and Module Constructionmentioning
confidence: 99%